Security Consideration in Information Management of Organization (Global Journal of Management and Business Research, 2014)
Information has become today the life-wire of every organization having the potential of determining the success or failure of the organization, irrespective of size. More so, it has become so valuable an as as assets which is constantly under threat of attack by modern technology. There is need for proper management information, for maximum 'utilization and benefit this paper thus discusses the security in information management, especially in corporate organizations. The operational environment of institution)' and organizations has become highly competitive, with each actor aiming at outsmarting others. Only enhanced knowledge of security, with its full implications understood would help any organizations to survive the competition and not washed out.